Fatigue response dependence of thickness measurement methods for additively manufactured E‐PBF Ti‐6Al‐4 V. Issue 7 (5th May 2021) - Segersäll, Mikael; Kerwin, Annie; Hardaker, Alex; Kahlin, Magnus; Moverare, Johan
Abstract: Light weight metal parts produced with additive manufacturing have gained increasing interest from the aerospace industry in recent years. However, light weight parts often require thin walls which can have different material properties compared to thick bulk material. In this work, the fatigue properties of Ti‐6Al‐4 V produced by electron beam powder bed fusion have been investigated for samples with three different wall thicknesses ranging from 1.3 to 2.7 mm and in three different directions; 0°, 45°, and 90° relative to the build plate. Generally, the 90° specimens show worse fatigue life compared to both 0° and 45°. It was found that the fatigue strength is lower for thin samples compared to thicker samples when the stress is calculated from nominal thickness or calliper measurements. However, since materials produced by electron beam powder bed fusion often have a rough as‐built surface, the load bearing area is not easy to determine. In this paper, four different methods for determining the load bearing area are presented. It is shown that if the surface roughness is considered when calculating the stress levels, the influence from specimen thickness decreases or even disappears.